RANCANGAN PENGELOLAAN SOCIAL MEDIA MARKETING ENGAGEMENT - Triana, Rinanda; Hidayah, Nurdin; Noerdjamal, Daeng (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p19, 2021)
This research intends to designed the engagement management of facebook and instagram of Management Unit of Jakarta Historical Museums formed by 3 major elements in managing social media interactions namely creator-related features, contextual features, and content features. This study used kualitatif method with descriptive approach by conducting interviews with companies and visitors, also observation on their social media. Which the results be analyzed using the Miles and Huberman analysis model and tested the validity of the data using source triangulation technique. The results of this research show that Management Unit of Jakarta Historical Museums has operator division in managing their social media consisting of coordinator and three admins, but there is no classification of admin’s job description in managing their social media. From both social media, the interaction that exists on facebook and instagram is still not optimal can be seen from the average number of likes and comment that has not shown a significant number. Interesting content for visitors is informative, provide detailed information, the right composition and layout, and use filters that are not excessive.